2014
DOI: 10.1002/fut.21687
|View full text |Cite
|
Sign up to set email alerts
|

A Factor Analytical Approach to the Efficient Futures Market Hypothesis

Abstract: Most empirical evidence suggests that the efficient futures market hypothesis, henceforth referred to as EFMH, stating that spot and futures prices should cointegrate with a unit slope on futures prices, does not hold, a finding at odds with many theoretical models. This article argues that these results can be attributed in part to the low power of univariate tests, and that the use of panel data can generate more powerful tests. The current article can be seen as a step in this direction. In particular, a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is well known that oil prices have impacts on consumer prices (e.g., Comley, 2014). In parallel, it is also demonstrated that oil and gold prices have a significant positive relationship Westerlund and Narayan, 2013;Westerlund et al, 2015). In addition, when oil prices increase, oil producers would have more cash to invest in gold.…”
Section: Literature Review: Is Gold a Hedge Against Inflation?mentioning
confidence: 98%
“…It is well known that oil prices have impacts on consumer prices (e.g., Comley, 2014). In parallel, it is also demonstrated that oil and gold prices have a significant positive relationship Westerlund and Narayan, 2013;Westerlund et al, 2015). In addition, when oil prices increase, oil producers would have more cash to invest in gold.…”
Section: Literature Review: Is Gold a Hedge Against Inflation?mentioning
confidence: 98%
“…Switzer and El-Khoury (2007) investigates the efficiency of the New York Mercantile Exchange (NYMEX) Division light sweet crude oil futures contract market and crude oil futures contract prices are found to be cointegrated with spot prices and unbiased predictors of future spot prices. Additionally, Westerlund, Norkute, and Narayan (2015) advance a factor analytical approach to the efficient futures market hypothesis. Additionally, Westerlund, Norkute, and Narayan (2015) advance a factor analytical approach to the efficient futures market hypothesis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Saberi et al, 2011 study the market efficiency and unbiasedness among WTI futures with different maturities tested. Additionally, Westerlund, Norkute, and Narayan (2015) advance a factor analytical approach to the efficient futures market hypothesis. Still, there is a limited amount of research that investigates the market efficiency in commodity futures markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second one is interested in the role of gold as a hedge against inflation (e.g., Batten et al, 2014;Bampinas and Panagiotidis, in press). The third one studies the informational efficiency of gold markets (e.g., GallaisHamonno et al, 2015;Narayan et al, 2010;Westerlund et al, 2015). The fourth one assesses the relationship between gold and other precious metals and commodities (e.g., Mensi et al, 2013;Narayan and Liu, 2011;Narayan et al, 2013).…”
Section: Introductionmentioning
confidence: 98%